Sondheim - Gottfried, Martin. 4 0 16; 5 ([New York] : H.N. Abrams, 1993)
This volume tells the complete story of Sondheim's remarkable career--from his earliest days under the wing of Oscar Hammerstein II, through his latest controversial musical, Assassins. In between is Sondheim's brilliant but largely unheralded work as a lyric writer for Leonard Bernstein (in West Side Story) and Jule Styne (in Gypsy), his first experience writing both music and lyrics (for A Funny Thing Happened on the Way to the Forum) and the legendary collaborations with producer Harold Prince. The author's narrative overview of Sondheim's life and his analysis of the music and lyrics are enhanced by numerous quotations from the composer/lyricist himself.
Portrait of the artist as a young man -- The crafts of lyrics and music -- Opening doors. Saturday Night, West Side Story, Gypsy -- Composer/ lyricist. A Funny Thing Happened on the Way to the Forum, Anyone can Whistle, Do I Hear a Waltz?, Evening Primrose -- The Prince collaborations- Part One: Company, Follies, A Little Night Music -- The Prince collaborations-Part Two. Pacific Overtures -- Sweeney Todd- The Demon Barber of Fleet Street, Merrily We Roll Along -- Everybody's got the right to be different. Sunday in the Park with George -- Into the Woods -- Assassins.
Keywords: 2 -- 0; 6; Sondheim, Stephen.;Sondheim, Stephen. Musicals; 20; 2